A high saturation magnetization zinc-doped nickel ferrite film and preparation method thereof
Through the preparation method of zinc-doped nickel ferrite film, the problems of poor crystal quality and low magnetization in spin electronic devices are solved, and high saturation magnetization and good crystallinity are achieved. Thin film improves spin filtration efficiency and device performance.
Patent Information
- Application Number
- CN202211135585.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-09-19
AI Technical Summary
In the application of spin electronic devices, existing nickel ferrite thin film materials have problems such as poor thin film crystal quality and low saturation magnetization, which affects spin filtration efficiency and device performance.
Through the preparation method of zinc-doped nickel ferrite film, zinc-doped nickel ferrite polycrystalline targets are synthesized by solid sintering method, and the film is grown on MgAl2O4 single crystal substrate by pulsed laser deposition to control zinc doping Content and deposition parameters to improve magnetic properties.
The produced zinc-doped nickel ferrite film has good crystallinity and high room temperature saturation magnetization, reaching 441.62emu/cm3, which is significantly better than the prior art and is expected to be used in spintronic devices in room temperature scenarios.
Smart Images

Figure CN115627527B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic semiconductor film materials, and in particular relates to a high saturation magnetization zinc-doped nickel ferrite film and a preparation method thereof. Background Art
[0002] In response to the information storage and logic operation needs of the post-Moore era, spintronic devices provide a promising direction for the development of the next generation of microelectronic devices with smaller unit size, non-volatility, low power consumption and high speed. These new devices can generate high spin polarization currents based on certain materials through spin filtering effects, etc., to achieve high-speed modulation and low-energy operation. Figure 1 A schematic diagram of the spin filtering effect is given, with non-magnetic metals on both sides and a spin filter layer in the middle. Electrons with random spin orientations are conducted from the Fermi level of the non-magnetic metal through the spin filter layer barrier to the metal with a lower Fermi level. The conduction band of the spin filter layer is split due to the exchange coupling between the conduction electrons and the magnetic atoms, which produces different barrier heights for electrons with spins up and down. Since the tunneling probability of conduction electrons in metals is negatively correlated with the barrier height, that is, the lower the barrier height, the greater the electron tunneling probability. Based on this, the importance of magnetic semiconductor materials in the application of spin electronic devices is self-evident.
[0003] In principle, ferromagnetic and ferrimagnetic semiconductors or insulator barriers all have a certain spin filtering ability. Among them, europium oxides (EuS, EuSe, EuO), perovskite manganese oxides (BiMnO3, La 0.1 Bi 0.9 MnO3) was observed to have spin filtering efficiency under low temperature conditions during the experiment, but the low Curie temperature of these barrier materials makes them difficult to apply in actual room temperature scenarios. Ferromagnetic spinel ferrite has a high magnetic transition temperature and is often used as a magnetic barrier material for spin filtering tunnel junctions. Relevant experimental and first-principles calculation studies have shown that spin filtering tunnel junctions with spinel ferrite materials (NiFe2O4, CoFe2O4) as barriers can generate spin polarized currents at room temperature.
[0004] In recent years, nickel ferrite thin film materials have become the preferred materials for spintronic devices due to their high resistivity, low eddy current loss, excellent chemical stability, and small lattice mismatch with typical ferromagnetic electrode materials. In view of the urgent need to develop spintronic devices based on nickel ferrite, it is necessary to conduct research on key scientific issues such as the preparation of high-quality nickel ferrite thin films and the regulation of doping performance. However, there are currently problems such as poor film crystal quality and low saturation magnetization. Therefore, by doping nickel ferrite, its magnetic properties are improved, thereby improving the spin filtering efficiency, providing a new direction for miniaturized, high-performance, and low-power spintronic devices. Summary of the invention
[0005] The object of the present invention is to provide a high saturation magnetization zinc-doped nickel ferrite film and a preparation method thereof.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for preparing a high saturation magnetization zinc-doped nickel ferrite film, wherein the film is (Ni 1-x Zn x )Fe2O4 film, wherein 0.25≤x≤1, the method comprises the following steps: mixing NiO, ZnO and Fe2O3 polycrystalline powders, using a solid sintering method, with a calcination heating rate of 5-20°C / min, a cooling rate of 3-5°C / min, a calcination temperature of 1050-1200°C, and a sintering time of 12-36h to obtain a disc-shaped zinc-doped nickel ferrite polycrystalline target; under the condition that the oxygen partial pressure is maintained at 1-10Pa, using the zinc-doped nickel ferrite polycrystalline target as the target material, using a pulsed laser deposition method, setting the laser energy to 200-400mJ, setting the pulse number to 20000-25000, the pulse frequency to 10Hz, and the target spacing to 4-6cm, to obtain the film on a MgAl2O4 single crystal substrate.
[0008] In a preferred embodiment of the present invention, the substrate is single-sided polished or double-sided polished and has a size of 5-10 mm×5-10 mm×0.4-0.6 mm.
[0009] In a preferred embodiment of the present invention, the thickness of the zinc-doped nickel ferrite film is 50-200 nm.
[0010] During the above pulse laser deposition process, the growth temperature of the film is 500-750°C.
[0011] The method for preparing the above-mentioned high saturation magnetization zinc-doped nickel ferrite film comprises the following steps:
[0012] (1) 0.5460-1.6612 g of NiO powder, 0.6033-2.3630 g of ZnO powder and 4.6370-4.7355 g of Fe2O3 were put into a mortar and ground and mixed evenly, then the mixed powder was poured into a stainless steel mold, pressed into shape by a cold press at a pressure of 8 MPa, and then calcined at 1050-1200°C for 12-36 h to obtain a ceramic target;
[0013] (2) Fixing the MgAl2O4 substrate on a sample heating table, and then placing it together with the target material into a vacuum chamber of a pulsed laser deposition device, and performing pulsed laser deposition at 500-750° C. to form the zinc-doped nickel ferrite film.
[0014] In a preferred embodiment of the present invention, the heating rate of the target material calcination in step (1) is 5-20°C / min, the cooling rate is 3-5°C / min, and the calcination temperature is 1050-1200°C.
[0015] In a preferred embodiment of the present invention, the pulsed laser deposition in step (2) specifically comprises:
[0016] a. Use a mechanical pump to pump the air pressure in the vacuum chamber to below 10Pa, and then use a molecular pump to pump the vacuum to 10 - 5 Pa;
[0017] b. Turn on the heater, heating rate is 10-25℃ / min, heat the sample stage to 500-750℃ and maintain constant temperature;
[0018] c. Open the flow controller to introduce oxygen into the vacuum chamber, use the bypass valve to fine-tune the pressure in the chamber to maintain the background oxygen partial pressure in the chamber at 1-10Pa, set the laser energy to 200-400mJ, set the number of pulses to 20000-25000, the pulse frequency to 10Hz, and the target distance to 4-6cm;
[0019] d. Use a baffle to block the sample heating stage, turn on the laser, pre-sputter the target for 8 minutes to remove surface contaminants, unscrew the baffle after the pre-sputtering, and formally start epitaxial growth on the MgAl2O4 substrate.
[0020] e. After the deposition is completed, the background oxygen partial pressure is maintained at 1-10Pa and the temperature is lowered at a rate of 10-25℃ / min;
[0021] f. Lower the temperature in the chamber to 200°C and use a molecular pump to evacuate the chamber to restore the back vacuum for 10 -5 Pa. The sample stage is taken out to obtain the above zinc-doped nickel ferrite thin film.
[0022] Each cation in nickel ferrite occupies the A position at the center of the crystal tetrahedron or the B position at the center of the octahedron. The ion distribution can be expressed as (M x Fe 1-x ) A [M 1-x Fe 1+x ] B O4, where M can be Ni in nickel ferrite 2+ or Fe 3+ Any cation with a stable ion valence. 2+ Occupies the B position at the center of the octahedron, Fe 3+There is no preference for the occupied position. However, Zn-doped nickel ferrite will change the occupation mode of Ni and Fe atoms at the A and B positions, change their coordination environment, and cause the exchange interaction between magnetic ions to change, thus leading to a huge change in magnetic properties. Therefore, the magnetic properties of the grown zinc-doped nickel ferrite film can be effectively controlled by changing the Zn doping content.
[0023] The applicant has found through research that, compared with other substrates (such as SrTiO3 substrates, MgO substrates, etc.), MgAl2O4 single crystal substrates have a higher crystal structure matching degree and a smaller lattice mismatch, and can obtain thin films with better performance.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The zinc-doped nickel ferrite film prepared by the present invention has good crystallinity, and its surface root mean square roughness is 0.1nm-0.4nm, showing a surface with atomic-level flatness. The film prepared above has insulating ferrimagnetism, and the room temperature saturation magnetization intensity is as high as 441.62emu / cm 3 , which is significantly superior to existing technologies and is expected to realize the application of spin electronic device materials in room temperature scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the spin filtering effect involved in the present invention.
[0027] Figure 2 It is a schematic diagram of the structure of zinc-doped nickel ferrite thin film samples prepared in Examples 1 to 4 of the present invention and Comparative Example 1.
[0028] Figure 3 3 are XRD diagrams of the thin film samples of Examples 1 to 4 of the present invention and Comparative Example 1, which are marked from top to bottom as Zn doping content x=0%, 25%, 50%, 75% and 100%.
[0029] Figure 4 is (Ni of Example 1 of the present invention 0.5 Zn 0.5 )Atomic force microscopy image of Fe2O4 thin film sample.
[0030] Figure 5 3 is the hysteresis loop diagram of Examples 1 to 4 of the present invention and Comparative Example 1 under room temperature conditions.
[0031] Figure 6 2 is an optical bandgap diagram of Examples 1 to 4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0033] Example 1
[0034] The specific preparation method of the high saturation magnetization zinc-doped nickel ferrite film of this embodiment is as follows:
[0035] (1) Target synthesis: 1.0997 g of NiO powder, 1.1981 g of ZnO powder and 4.7022 g of Fe2O3 powder (i.e., Zn doping content of 50%) were weighed and put into a mortar and ground to mix evenly. The evenly mixed powder was then poured into a stainless steel grinder and pressed into a round cake with a diameter of 1 inch using a tablet press at a pressure of 8 MPa. The round cake was then placed in a high-temperature muffle furnace and calcined at 1100°C for 24 h with a heating rate of 10°C / min and a cooling rate of 5°C / min.
[0036] (2) A 5×5 mm single-sided polished MgAl2O4 substrate was fixed on a sample heating table with silver glue and baked at 200°C for 15 min. After the silver glue was completely dry, the sample heating table was placed in the vacuum chamber of the pulsed laser deposition system.
[0037] (3) Adjust the distance between the target and the substrate to 50 mm. First, use a mechanical pump to pump the pressure in the chamber to below 10 Pa, and then use a molecular pump to pump the vacuum to 10 -5 Pa. Turn on the heater, raise the temperature of the sample heating stage to 650°C at a heating rate of 25°C / min and maintain the temperature constant.
[0038] (4) Turn on the flow controller to introduce oxygen into the vacuum chamber, and use the bypass valve to fine-tune the pressure in the chamber to maintain the background oxygen partial pressure in the chamber at 2.7 Pa. Set the laser energy to 300 mJ, the number of pulses to 21,000 pulses, the pulse frequency to 10 Hz, and the target spacing to 5 cm. Use a baffle to block the sample heating stage, turn on the laser, and first use the laser to bombard the target for 8 minutes to remove surface contaminants. After the end, unscrew the baffle and start formally depositing the film on the MgAl2O4 substrate.
[0039] (5) After the deposition is completed, the background oxygen partial pressure is maintained at 2.7 Pa, and the sample heating stage is cooled to below 200°C at a cooling rate of 25°C / min. A molecular pump is then used to evacuate the chamber to restore the background vacuum for 10 -5 Pa. Take out the sample heating stage and obtain a 100nm thick (Ni 0.5 Zn 0.5 )Fe2O4 film, the obtained structure is as follows Figure 2 As shown, it includes a MgAl2O4 substrate and a (Ni 1-x Zn x )Fe2O4 film.
[0040] Example 2
[0041] A high saturation magnetization zinc-doped nickel ferrite film for comparison was prepared in a method substantially the same as in Example 1, except that 1.6612 g of NiO powder, 0.6033 g of ZnO powder and 4.7355 g of Fe2O3 powder were weighed in the target material synthesis step (1), i.e., the Zn doping content was 25%, and the pulse number was set to 20000 pulses in step (4), to obtain a 100 nm thick (Ni2O3) film. 0.75 Zn 0.25 )Fe2O4 film.
[0042] Example 3
[0043] A high saturation magnetization zinc-doped nickel ferrite film for comparison was prepared in a method substantially the same as in Example 1, except that 0.5460 g of NiO powder, 1.7847 g of ZnO powder and 4.6693 g of Fe2O3 powder were weighed in step (1) of target material synthesis, i.e., the Zn doping content was 75%, and the number of pulses was set to 22000 pulses in step (4) to obtain a 100 nm thick (Ni2O3) film. 0.25 Zn 0.75 )Fe2O4 film.
[0044] Example 4
[0045] A high saturation magnetization zinc-doped nickel ferrite film for comparison was prepared in substantially the same manner as in Example 1, except that 2.3630 g of ZnO powder and 4.6370 g of Fe2O3 powder were weighed in the target synthesis step (1), i.e., the Zn doping content was 100%, and the pulse number was set to 23,000 pulses in step (4) to obtain a ZnFe2O4 film with a thickness of 100 nm.
[0046] Comparative Example 1
[0047] A high saturation magnetization zinc-doped nickel ferrite film for comparison was prepared in accordance with a method substantially the same as in Example 1, except that 2.2308 g of NiO powder and 4.7692 g of Fe2O3 powder were weighed in the target material synthesis step (1), i.e., the Zn doping content was 0%, and the pulse number was set to 24000 pulses in step (4) to obtain a NiFe2O4 film with a thickness of 100 nm.
[0048] Comparative Example 2
[0049] A high saturation magnetization zinc-doped nickel ferrite film for comparison was prepared in the same manner as in Example 1, except that in step (2), the substrate used was a SrTiO3 substrate, and a 100 nm thick (Ni 0.5 Zn 0.5 )Fe2O4 film.
[0050] Comparative Example 3
[0051] A high saturation magnetization zinc-doped nickel ferrite film for comparison was prepared in the same manner as in Example 1, except that in step (2), the substrate used was a MgO substrate, and a 100 nm thick (Ni 0.5 Zn 0.5 )Fe2O4 film.
[0052] Figure 3 The XRD graphs of the nickel ferrite thin film samples doped with different contents of zinc prepared in Examples 1 to 4 of the present invention and Comparative Example 1 are given. The two diffraction peaks in the graph are the sample peak and the (004) diffraction peak of the MgAl2O4 substrate from left to right. The peak positions of the thin film samples prepared in Examples 1 to 4 and Comparative Example 1 gradually move toward low θ values as the Zn doping content increases, indicating that the out-of-plane lattice constant of the film gradually increases, which is caused by the compressive stress of the substrate on the film. At the same time, the above zinc-doped nickel ferrite thin film has good crystallinity.
[0053] Figure 4 The (Ni) prepared in Example 1 of the present invention is given. 0.5 Zn 0.5 )Atomic force microscopy image of the Fe2O4 thin film sample, with a root mean square roughness of 0.2nm, showing an atomically smooth and uniform morphology.
[0054] Figure 5 The hysteresis loops of the nickel ferrite film samples doped with different contents of zinc prepared in Examples 1 to 4 of the present invention and Comparative Example 1 at room temperature are given. It can be seen that when the Zn doping content is 50%, the film prepared in Example 1 has insulating ferrimagnetism, and its room temperature saturation magnetization intensity is the largest, up to 441.62emu / cm 3 , which has great advantages compared with the existing technology.
[0055] The magnetic test results of Example 1 and Comparative Examples 2 to 3 are shown in the following table:
[0056]
[0057] The test results show that: the (Ni 0.5 Zn 0.5)The room temperature saturation magnetization intensity of the Fe2O4 film is significantly better than that of Comparative Example 2 and Comparative Example 3, indicating that for the zinc-doped nickel ferrite film, the MgAl2O4 single crystal substrate has a high crystal structure matching degree and a smaller lattice mismatch degree than the other two substrates.
[0058] Figure 6 The optical band gap diagrams of the nickel ferrite thin film samples doped with different contents of zinc prepared in Examples 1 to 4 of the present invention and Comparative Example 1 are given. It can be seen that with the increase of the Zn doping content, compared with Comparative Example 1, the band gap of the thin films prepared in Examples 1 to 4 gradually increases from 2.74 eV to 3.19 eV, which provides the possibility for realizing a larger exchange splitting difference in spin filter materials, and is expected to promote the development and application of spin electronics devices.
Claims
1. A method for preparing a high saturation magnetization zinc-doped nickel ferrite film, wherein the film is (Ni 1-x Zn x )Fe2O4 film, wherein 0.25≤x≤1, the method comprises the following steps: mixing NiO, ZnO and Fe2O3 polycrystalline powders, using a solid sintering method, with a calcination heating rate of 5-20°C / min, a cooling rate of 3-5°C / min, a calcination temperature of 1050-1200°C, and a sintering time of 12-36h to obtain a disc-shaped zinc-doped nickel ferrite polycrystalline target; under the condition that the oxygen partial pressure is maintained at 1-10Pa, using the zinc-doped nickel ferrite polycrystalline target as the target material, using a pulsed laser deposition method, setting the laser energy to 200-400mJ, setting the pulse number to 20000-25000, the pulse frequency to 5-10Hz, and the target spacing to 4-6cm, to obtain the film on a MgAl2O4 single crystal substrate.
2. The method for preparing a high saturation magnetization zinc-doped nickel ferrite thin film according to claim 1, characterized in that: The MgAl2O4 single crystal substrate is single-sided polished or double-sided polished.
3. The method for preparing a high saturation magnetization zinc-doped nickel ferrite thin film as claimed in claim 2, characterized in that: The size of the MgAl2O4 single crystal substrate is 5-10 mm×5-10 mm×0.4-0.6 mm.
4. The method for preparing a high saturation magnetization zinc-doped nickel ferrite thin film according to claim 1, characterized in that: The 1-x Zn x )The thickness of the Fe2O4 film is 50-200nm.
5. The method for preparing a high saturation magnetization zinc-doped nickel ferrite thin film according to claim 1, characterized in that: During the pulse laser deposition process, the growth temperature of the film is 500-750°C.
6. A method for preparing a high saturation magnetization zinc-doped nickel ferrite thin film according to any one of claims 1 to 5, characterized in that: The steps include: (1) 0.5460-1.6612 g of NiO powder, 0.6033-2.3630 g of ZnO powder and 4.6370-4.7355 g of Fe2O3 were put into a mortar and ground and mixed evenly, and then the mixed powder was poured into a stainless steel mold, pressed into shape by a cold press at a pressure of 8 MPa, and then calcined at 1050-1200°C for 12-36 h, with heating and cooling rates of 5-20°C / min and 3-5°C / min, respectively, to obtain a ceramic target; (2) Fixing the clean MgAl2O4 substrate on a sample heating table, and then placing it together with the target material into a vacuum chamber of a pulsed laser deposition system, and performing pulsed laser deposition at 500-750° C. to form the zinc-doped nickel ferrite film.
7. The preparation method according to claim 6, characterized in that: The target material calcination in step (1) has a heating rate of 5-20°C / min, a cooling rate of 3-5°C / min, a calcination temperature of 1050-1200°C, and a sintering time of 12-36h.
8. The preparation method according to claim 6, characterized in that: The pulsed laser deposition in step (2) specifically includes: a. Use a mechanical pump to pump the air pressure in the vacuum chamber to below 10Pa, and then use a molecular pump to pump the vacuum to 10 -5 Pa; b. Turn on the heater at a heating rate of 10-25°C / min, raise the temperature of the sample heating stage to 500-750°C and maintain a constant temperature; c. Open the flow controller to introduce oxygen into the vacuum chamber, use the bypass valve to fine-tune the pressure in the chamber to maintain the background oxygen partial pressure in the chamber at 1-10Pa, set the laser energy to 200-400mJ, set the number of pulses to 20000-25000, the pulse frequency to 10Hz, and the target distance to 4-6cm; d. Use a baffle to block the sample heating stage, turn on the laser, pre-sputter the target for 5-10 minutes to remove surface contaminants, unscrew the baffle after the pre-sputtering, and formally start epitaxial growth on the MgAl2O4 substrate; e. After the deposition is completed, the background oxygen partial pressure is maintained at 1-10Pa and the temperature is lowered at a rate of 10-25℃ / min; f. Lower the temperature in the chamber to 200°C and use a molecular pump to evacuate the chamber to restore the back vacuum for 10 -5 Pa, take out the sample heating stage, and obtain the above-mentioned zinc-doped nickel ferrite thin film.
9. A high saturation magnetization zinc-doped nickel ferrite film, prepared according to the preparation method according to any one of claims 1 to 8.
10. The high saturation magnetization zinc-doped nickel ferrite film according to claim 9, wherein the room temperature saturation magnetization reaches 441.62emu / cm 3 .